Case reportA case of dilated cardiomyopathy associated with coeliac disease - Glover, Benedict M.; Treanor, Nuala J.; McEneaney, David J. (Archives of Medical Science, 2007)
Dilated cardiomyopathy in association with coeliac disease has been rarely reported in the past. We describe a case of dilated cardiomyopathy in a young patient in which all other causes were excluded. The patient was found to have previously undiagnosed coeliac disease and had a good improvement in symptoms as well as left ventricular function and dimensions as a result of a gluten free diet. It may be worthwhile considering checking a coeliac serology in patients who present with a dilated cardiomyopathy as it is a simple investigation and has considerable implications on overall management and perhaps prognosis.